2015
DOI: 10.1007/s00018-015-2048-2
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin promotes oral tumor cell proliferation by modifying GLUT1 expression

Abstract: In our study, ghrelin was investigated with respect to its capacity on proliferative effects and molecular correlations on oral tumor cells. The presence of all molecular components of the ghrelin system, i.e., ghrelin and its receptors, was analyzed and could be detected using real-time PCR and immunohistochemistry. To examine cellular effects caused by ghrelin and to clarify downstream-regulatory mechanisms, two different oral tumor cell lines (BHY and HN) were used in cell culture experiments. Stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Cells (800 000/dish) were stimulated with A. actinomycetemcomitans and P. gingivalis for 30 or 120 minutes. Western blot and analysis were performed as described previously . The following primary antibodies were used: rabbit IgG anti‐p38 (dilution 1:1000) and rabbit IgG anti‐phospho‐p38 (dilution 1:1000), rabbit IgG anti‐ERK1/2 (dilution 1:1000), and rabbit IgG anti‐phospho‐ERK1/2 (dilution 1:1000).…”
Section: Methodsmentioning
confidence: 99%
“…Cells (800 000/dish) were stimulated with A. actinomycetemcomitans and P. gingivalis for 30 or 120 minutes. Western blot and analysis were performed as described previously . The following primary antibodies were used: rabbit IgG anti‐p38 (dilution 1:1000) and rabbit IgG anti‐phospho‐p38 (dilution 1:1000), rabbit IgG anti‐ERK1/2 (dilution 1:1000), and rabbit IgG anti‐phospho‐ERK1/2 (dilution 1:1000).…”
Section: Methodsmentioning
confidence: 99%
“…We found that the ghrelin expression level in OSCC was lower than those in oral epithelial tissue and leukoplakia; moreover, the ghrelin expression in OSCC was found especially in keratin pearls. In the second study, Kraus et al 15 found increased expression of ghrelin and its receptors in OSCC compared with healthy gingiva and benign tissue. The studies evaluating OSCC ghrelin levels yielded conflicting results.…”
Section: Fig 2cmentioning
confidence: 96%
“…In our samples, all the oral leukoplakia showed hyperkeratosis without dysplasia. The histologic diagnosis of oral leukoplakia was not mentioned in Kraus et al 15 It is possible that the ghrelin level begins to change with dysplastic changes in oral leukoplakia. Recently, it is stated inflammatory conditions of oral mucosa is one of the biggest challenges to distunguish bening lesions from potentially malignant lesions, and dysplastic/malignant ones from inflammatory conditions.…”
Section: Fig 2cmentioning
confidence: 99%
See 2 more Smart Citations